Taking Direction: New Dramaturgies of Science from the Splice Symposium and the Performing Science Conference. (September 2014) - Mermikides, Alex
<x content-type="archive" xml:space="preserve">Abstract</x> This short article responds to two recent conferences on performance and science: the Splice Symposium (Chimera Network/University of Notre Dame) and Performing Science (University of Lincoln). Rather than a conventional conference report, the author reflects on a selection of presentations in the light of issue one of ISR's 'theatre and science' series.